Inversion of Uterus - Presenting as a Complication of Abortion - Begum, Nazneen; Ganguly, Shikha; Anwer, Begum Rokeya; Islam, Ferdousi (Bangladesh Journal of Obstetrics & Gynaecology, 2016)
Abstract not available Bangladesh J Obstet Gynaecol, 2014; Vol. 29(1) : 54-55